2021
DOI: 10.1109/access.2021.3066538
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Detection Framework About Conditions of Wearing Face Mask for Helping Control the Spread of COVID-19

Abstract: Properly wearing a face mask has become an effective way to limit the COVID-19 transmission. In this work, we target at detecting the fine-grained wearing state of face mask: face without mask, face with wrong mask, face with correct mask. This task has two main challenging points: 1) absence of practical datasets, and 2) small intra-class distance and large inter-class distance. For the first challenging point, we introduce a new practical dataset covering various conditions, which contains 8635 faces with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…Single-stage methods based on deep learning techniques account for the largest proportion among the methods. They include Faster R-CNN [23], [77], Context-Attention R-CNN [47], InceptionV3 [78], MobileNet [60], SSD [79], YOLO [80], YOLOv2 [42], YOLOv3 [26], [29], [50], [81], [82], YOLOv4 [31], [51], [83], [84], YOLOv5 [85]- [88], and others [11], [41], [46], [52], [89]- [94], etc. It can be clearly concluded that YOLO and its variants are used widely.…”
Section: B Single-stage (End-to-end) Methodsmentioning
confidence: 99%
“…Single-stage methods based on deep learning techniques account for the largest proportion among the methods. They include Faster R-CNN [23], [77], Context-Attention R-CNN [47], InceptionV3 [78], MobileNet [60], SSD [79], YOLO [80], YOLOv2 [42], YOLOv3 [26], [29], [50], [81], [82], YOLOv4 [31], [51], [83], [84], YOLOv5 [85]- [88], and others [11], [41], [46], [52], [89]- [94], etc. It can be clearly concluded that YOLO and its variants are used widely.…”
Section: B Single-stage (End-to-end) Methodsmentioning
confidence: 99%
“…The technologies discussed are deep learning associated with X-ray, in vitro diagnostics (IVDs), and wearable sensors based on IoT for monitoring the COVID-19 patients. In [ 17 ], detection of the face wearing mask in the fine state has been done with context attention R-CNN technique with the help of special features for the purpose of region proposal and by dissociation of localization and classification fields. The context approach R-CNN has been found to be highly accurate.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, the R-CNN slowly performs a ConvNet forward pass for each object proposal without sharing computation. Zhang et al [104] proposed a context-attention R-CNN as a detection framework of wearing face masks. This framework is used to expand the intra-class distance and reduce the inter-class distance by extracting distinguishing features.…”
Section: Mask Detectionmentioning
confidence: 99%
“…MaskTheFace [31] MaskedFace-Net [32], DCNN [33], CYCLE-GAN [34], IAMGAN [35], starGAN [36], segments [39][40][41], regularization [42], sparse rep. [43] Domain-specific models FaceNet [83], SphereFace [8], MFCosface [85], VGGFace [48], DeepID [86], LSTM-autoencoders [70], DC-SSDA [71], de-corrupt autoencoders [72], 3D autoencoder [73], pose invariant FR [77], makeup-invariant [78], DBNs [79,80], attention-aware [82], margin-aware [15] Feature extraction LBPs [44], SIFT [45], HOG [89], codebooks [90], multi-stage mask learning strategy [92], attention-aware and context-aware [93][94][95], GCN [96][97][98] Mask detection R-CNN [101], Fast R-CNN [102], Faster R-CNN [103], context-attention R-CNN [104], FCN [105], U-Net [106], FAN [109], LLE-CNNs [110], ...…”
Section: Conflicts Of Interestmentioning
confidence: 99%